Chemical industrial kilns used for co-processing of hazardous waste: Low environmental risks of polycyclic aromatic hydrocarbons (PAHs). Issue 5 (October 2020) - Li, Xuebing; Li, Li; Du, Yuying; Liu, Meijia; Huang, Qifei; Yang, Jinzhong; Tang, Lianghua; Yan, Dahai
Graphical abstract: Highlights: Chemical industrial kilns can be used for co-processing of hazardous waste. Co − processing of hazardous waste in CWSG has little effect on the operating stability of the gasifier. Low environmental risks of PAHs in CWSG during co − processing process. LMW PAHs mainly distributed in exhaust gas, MMW and HMW PAHs mainly distributed in solid waste. Abstract: Chemical industrial kilns were found to be used for waste treatment, however it is still in the research stage. In our study, field tests were conducted to find the emission and distribution characteristics of polycyclic aromatic hydrocarbons (PAHs) during co-processing of hazardous waste in an industrial scale coal-water slurry gasifier (CWSG), which is applied to ammonia production. Changes of temperature, pressure and gas production of CWSG were recorded under both blank condition (i.e., regular production) and test condition (i.e., feedstock mixed with hazardous waste). Concentration of PAHs in all the solid waste, waste water, and exhaust gas under two conditions were analyzed. Results showed that co-processing of hazardous waste has little impact on the operation stability of CWSG, the temperature were ranged at 1330–1350 ℃ in CWSG, the pressure and gas production were stabled at 1.0–1.3 MPa and 12, 000–14, 000 Nm 3 /h respectively. Low environmental risks of PAHs in regular production and weren't increased by the addition of hazardous waste. Distribution trends of PAHs with different molecular weights in solid-liquid-gas three phases were basically the same under both two conditions. 92.96 %−93.68 % low molecular weights (LMW, 2–3rings) PAHs distributed in exhaust gas, 50.84 %−71.66 % middle molecular weights (MMW, 4 rings) PAHs distributed in solid waste, and 85.3 %−86.77 % high molecular weight (HMW, 5–6 rings) PAHs distributed in solid waste, while the content of PAHs in waste water was generally low.